Enabling communities for a changing climate: Re-configuring spaces of hazard governance. Issue 100 (March 2019) - Barr, Stewart; Woodley, Ewan
Abstract: The last ten years have witnessed increasing levels of concern and public debate about the risks associated with environmental hazards such as flooding in the UK and the likelihood that these will increase in frequency due to anthropogenic climate change. In this paper, we argue that attempts to mitigate this process through a focus on individualised risk communication and behavioural change are unlikely to be successful, given the epistemic conflicts surrounding climate change knowledges in public discourse. In response, we argue for an alternative framework for developing environmental knowledges, using social learning to promote both epistemic re-alignment and a re-scaling of environmental governance that promotes enablement. We use insights from research on flooding in South West England to highlight the ways in which traditional policy approaches such as behavioural change have come to be so overbearing in public debate on environmental hazards management. In contrast, we demonstrate the potential for a re-scaling of environmental governance to reconfigure climate change knowledge and build new spaces for enablement to reduce hazard vulnerability at the place-based community scale. We argue that this has major epistemological and practical implications for the ways that researchers and policy makers work with publics to reduce hazard risk under a changing climate.